The Value of Reality to Logic and the Value of Logic to Reality: A Comparison of Łukasiewicz’s and Leśniewski’s Views - Rybaříková, Zuzana (Filozofia Nauki, 2022)
Since Kazimierz Twardowski introduced the notions of “symbolomania” and “pragmatophobia,” the relationship between logic and reality was the focus of the philosophers from the Lvov-Warsaw School — inter alia two prominent logicians of the group, Stanisław Leśniewski and Jan Łukasiewicz. Bolesław Sobociński has pointed out, however, that there was a contrast between their approach to logic and reality. Despite being members of the same philosophical group and even colleagues from the same department, their philosophical views on the position of logic in reality differed considerably. Yet they both agreed that reality has a certain importance for logic and that logic could be valuable for reality. The aim of this paper is to introduce their divergent positions and describe in more detail how Leśniewski and Łukasiewicz understood the relationship between logic and the real world.